Genetic Regulation of Guanylate-Binding Proteins 2b and 5 during Leishmaniasis in Mice - Sohrabi, Yahya; Volkova, Valeryia; Kobets, Tatyana; Havelková, Helena; Krayem, Imtissal; Slapničková, Martina; Demant, Peter; Lipoldová, Marie (Frontiers in Immunology, 2018)
Interferon-induced GTPases (guanylate-binding proteins, GBPs) play an important role in inflammasome activation and mediate innate resistance to many intracellular pathogens, but little is known about their role in leishmaniasis. We therefore studied expression of Gbp2b/Gbp1 and Gbp5 mRNA in skin, inguinal lymph nodes, spleen and liver after Leishmania major infection and in uninfected controls. We used two different groups of related mouse strains: BALB/c, STS and CcS-5, CcS-16 and CcS-20 that carry different combinations of BALB/c and STS genomes, and strains O20, C57BL/10 (B10) and B10.O20, OcB-9 and OcB-43 carrying different combinations of O20 and B10 genomes. The strains were classified on basis of size and number of infection-induced skin lesions as highly susceptible (BALB/c, CcS-16), susceptible (B10.O20), intermediate (CcS-20), and resistant (STS, O20, B10, OcB-9, OcB-43). Some uninfected strains differed in expression of Gbp2b/Gbp1 and Gbp5, especially of Gbp2b/Gbp1 in skin. Uninfected BALB/c and STS did not differ in their expression, but in CcS-5, CcS-16, CcS-20, which all carry BALB/c-derived Gbp gene-cluster, expression of Gbp2b/Gbp1 exceeds that of both parents. These data indicate trans-regulation of Gbps. Infection resulted in approximately 10x upregulation of Gbp2b/Gbp1 and Gbp5 mRNAs in organs of both susceptible and resistant strains, which was most pronounced in skin. CcS-20 expressed higher level of Gbp2b/Gbp1 than both parental strains in skin, whereas CcS-16 expressed higher level of Gbp2b/Gbp1 than both parental strains in skin in liver. This indicates a trans-regulation present in infected mice CcS-16 and CcS-20. Immunostaining of skin of five strains revealed in resistant and intermediate strains STS, CcS-5, O20, and CcS-20 tight co-localization of Gbp2b/Gbp1 protein with most L. major parasites, whereas in the highly susceptible strain BALB/c most parasites did not associate with Gbp2b/Gbp1. Conclusion: Expression of Gbp2b/Gbp1 and Gbp5 was increased even in organs of clinically asymptomatic resistant mice. It suggests a hidden inflammation, which might contribute to control of persisting parasites. This is supported by the co-localization of Gbpb2/Gbp1 protein and L. major parasites in skin of resistant and intermediate but not highly susceptible mice.